2015
DOI: 10.1086/682227
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Capillary Hemangiomatosis: The Role of Invasive Cardiopulmonary Exercise Testing

Abstract: Pulmonary capillary hemangiomatosis (PCH) is a rare form of pulmonary arterial hypertension (PAH) characterized by pulmonary capillary proliferation and pseudoinvasion of collagenous septal structures. PCH is often accompanied by veno-occlusive changes and pulmonary hypertensive arterial remodeling. The clinical and pathological diagnosis of PCH can be subtle and easily missed. Most reported cases of PCH have been associated with resting PAH. We report the cases of 3 patients who initially presented with exert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Because of these constraints, pulmonary capillary dysfunction is inferred using indirect means, such as tissue density via computed tomography (CT) or invasive left heart catheterization (7,14). Imaging modalities such as CT and MRI can be used to quantify dynamics in the larger pulmonary vasculature (14) and are used extensively in subjects with pulmonary hypertension (10,12) and interstitial lung disease (49).…”
Section: Introductionmentioning
confidence: 99%
“…Because of these constraints, pulmonary capillary dysfunction is inferred using indirect means, such as tissue density via computed tomography (CT) or invasive left heart catheterization (7,14). Imaging modalities such as CT and MRI can be used to quantify dynamics in the larger pulmonary vasculature (14) and are used extensively in subjects with pulmonary hypertension (10,12) and interstitial lung disease (49).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of normal capillary structure would also affect both pulmonary hemodynamics and gas exchange. These abnormal capillaries have been reported in several conditions with a pathologic picture reminiscent of the PCH‐PVOD spectrum of disease and are often associated with clinically progressive PH and hypoxemia .…”
Section: Discussionmentioning
confidence: 85%
“… 1 This hemodynamics clearly shows progression of disease over the last three years. Dubrock et al 16 reported three cases of unexplained dyspnea where cardiopulmonary exercise testing suggested pulmonary vascular disease. Subsequent lung biopsy confirmed PCH.…”
Section: Discussionmentioning
confidence: 99%